HUBUNGAN STATUS GIZI DENGAN HASIL BELAJAR SISWA KELAS I SD NEGERI 5 BANDA ACEH - Awaluddin Awaluddin.; Tursinawati Tursinawati.; Nurmayitah Nurmasyitah. (Jurnal Pesona Dasar, 2017)
School children fall into the category of nutrition-prone so that they need fulfillment of nutrition elements because they can affect physical growth and brain development. This relates to learning process and optimum learning achievement. The research concerns the problems on the correlation between nutrition status and first-grade students’ achievements of Elementary School 5 Banda Aceh. The research aims at finding out the correlation between nutrition status and learning outcome of first-grade students of Elementary School 5 Banda Aceh. The hypothesis is that there is a correlation between nutrition status and learning results of first-graders of Elementary School 5 Banda Aceh. It used quantitative method with correlation research type. It took place at Elementary School 5 Banda Aceh with 53 samples that was taken from 2 classes, namely IA and IB. The data collection of nutrition status is obtained from body weight measurement and body height measurement, which later are analyzed using body mass index formula based on age (BMI/A) and threshold formula (z-score)to interpret nutrition status, meanwhile the learning results is obtained by taking the students’ mean score of mid-semester examination. Statistical test that is used here is Product Moment correlation test and hypothesis test using z-test with significance of 0.05 (5%). Based on the data analysis results, a description of student’s nutrition status clinically is normal on the criterion of good nutrition with an average of -1,3 and learning outcomes are on the criterion of adequate with an average of 6.5.From the result of correlation analysis between nutrition status and student’s learning result, there is 0.466 correlation value that includes in the criterion of moderate and hypothesis test result is z count (3.36) z table (1.96), so that Ha is accepted. Therefore, in conclusion, there is a correlation between nutrition status and learning result of first-grade of Elementary School 5 Banda Aceh.